THE EFFECT OF EGGSHELL MOSAIC TRAINING TOWARD FINE MOTOR SKILLS OF CHILDREN WITH INTELLECTUAL AND DEVELOPMENTAL DISABILITY (IDD) - Finalistiani, Diadra; AM, M Shodiq (Department of Special Education, 2016)
The purpose of this research was to determine the effect of eggshell mosaic toward fine motor skills of children with intellectual and develompental disability. The data was collected with observation, and the analysis technique used analysis in condition and analysis between conditions. The conclusion of this research was eggshell mosaic gives effect toward the fine motor skills of the children, it was shown from fine motor skills of the children before eggshell mosaic treatment, during the treatment and after controlling, and the fine motor skills of the children was improved.